Non‐isolated interleaved bidirectional DC–DC converter with high step voltage ratio and minimum number of switches. Issue 6 (11th March 2019) - Shaneh, Mahdi; Niroomand, Mehdi; Adib, Ehsan
Abstract : In this study, a new non‐isolated interleaved bidirectional DC–DC converter with a high step voltage ratio based on coupled inductors (CIs) is introduced. The CIs significantly increase the voltage conversion ratio and provide soft‐switching conditions for the switches at turn‐on instant. Also, employing an interleaved structure combined with the CI in the low‐voltage side noticeably reduces the current ripple and this feature has a vital role in the high‐power applications. Also, this topology provides auto‐current sharing for the two phases of the interleaved structure. The CIs in the high‐voltage side, supply a steep gain in both buck and boost modes with an appropriate duty cycle. The proposed method provides zero current switching (ZCS) turn‐off condition for all diodes and ZCS turn‐on condition for all switches without requiring any auxiliary circuit. So the undesirable reverse recovery effects of diodes are considerably reduced. The proposed converter has the minimum number of switches for two‐phase bidirectional structures. Also, a simple passive clamp circuit is proposed for the converter to limit the voltage spikes of CIs. Finally, a 600 W, 30/300 V laboratory prototype is implemented to verify the performance.